2019
DOI: 10.1038/s41598-019-49179-w
|View full text |Cite
|
Sign up to set email alerts
|

The pathohistological subtype strongly predicts survival in patients with ampullary carcinoma

Abstract: Ampullary cancer represents approximately 6% of the malignant periampullary tumors. An early occurrence of symptoms leads to a 5-year survival rate after curative surgery of 30 to 67%. In addition to the tumor stage, the immunohistological subtypes appear to be important for postoperative prognosis. The aim of this study was to analyze the different subtypes regarding their prognostic relevance. A total of 170 patients with ampullary cancer were retrospectively analyzed between 1999 until 2016 after pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 37 publications
7
36
1
6
Order By: Relevance
“…For instance, Vilhordo and colleagues ( 9 ) discovered the four prognostic factors of lymph node metastasis number, lymph node ratio (LNR), lymphovascularization, and differentiation grade of invasion. Numerous reports ( 10 , 11 ) have also reported that the histological type is associated with overall survival, implicating poor prognosis for the pancreaticobiliary-type, as observed in our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, Vilhordo and colleagues ( 9 ) discovered the four prognostic factors of lymph node metastasis number, lymph node ratio (LNR), lymphovascularization, and differentiation grade of invasion. Numerous reports ( 10 , 11 ) have also reported that the histological type is associated with overall survival, implicating poor prognosis for the pancreaticobiliary-type, as observed in our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…In Deutschland ist der intestinale Subtyp mit 34,5 % seltener, ein pankreatobiliärer Subtyp liegt in 58 % der Fälle vor. In 7,6 % der Fälle liegt ein gemischter Typ vor [23]. Ähnliche Ergebnisse ergab eine kleine Serie aus Serbien mit 37 Patienten mit einem Anteil für den pankreatobiliären Subtyp von 62 % und 35 % für den intestinalen Subtyp, in 3 % der Fälle lag ein gemischter Typ vor [24].…”
Section: Caveunclassified
“…Das Langzeitüberleben ist bei Patienten mit intestinalem Subtyp am besten, gefolgt vom gemischten Typ. Patienten mit pankreatobiliärem Subtyp haben die schlechteste Prognose [21,23,24,28]. Die immunhistochemische Differenzierung der histologischen Subtypen ist demzufolge sowohl für die Wahl der adjuvanten Chemotherapie als auch für die Prognose relevant [27].…”
Section: Caveunclassified
“…Due to these considerations, an accurate histological classification of AACs is crucial for management by a tailored therapeutic strategy and valid prognostic asse-ssment[ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%